2012
DOI: 10.1111/j.1468-2435.2011.00732.x
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Guilt and Stigma: Changing Attitudes among Israeli Migrants in Canada

Abstract: Over 60 years ago, the Jewish nationalist movement known as Zionism culminated in the creation of the State of Israel. Millions of Jews immigrated to Israel over the twentieth century, a process known as aliya (literally, “going up”). Yet over the years, thousands of Israelis have also chosen to leave Israel in a movement termed yerida (“going down”). As the term suggests, this reverse migration has been highly stigmatized. During the 1960s and 1970s, emigrants were publicly disparaged in the Israeli media for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 25 publications
0
1
1
Order By: Relevance
“…Migrants, today, have been found to be more critical of Israel (Hart, 2004) expressing nuanced and more individualised motivations for their mobility. This challenges previous scholarship that found where more collectivist drivers were articulated by both Jewish and Israeli diaspora communities in relation to the state of Israel and the need to collectively organise and support one another in different host countries (Harris, 2015;Harpaz, 2013).…”
Section: The Study Contextcontrasting
confidence: 76%
See 1 more Smart Citation
“…Migrants, today, have been found to be more critical of Israel (Hart, 2004) expressing nuanced and more individualised motivations for their mobility. This challenges previous scholarship that found where more collectivist drivers were articulated by both Jewish and Israeli diaspora communities in relation to the state of Israel and the need to collectively organise and support one another in different host countries (Harris, 2015;Harpaz, 2013).…”
Section: The Study Contextcontrasting
confidence: 76%
“…Gold and Hart (2013) claim that Israeli migrants (the Israeli diaspora) tend to resist full integration into the host societies, viewing their stay abroad as a temporary venture due to Zionist ideology which demands that Jews should live in their historical homeland, the state of Israel. However, recent studies on Israeli emigration (Gold & Hart, 2013;Harris, 2015) have found increased migration of highly skilled and educated Israeli-born population, and argued that the rationales for migration are no longer purely financial but also display ideological motivations, specifically in relation to a disapproval of current right-wing governments' approach to managing the Palestinian-Israeli conflict, and a lack of hope that it will ever be resolved. Migrants, today, have been found to be more critical of Israel (Hart, 2004) expressing nuanced and more individualised motivations for their mobility.…”
Section: The Study Contextmentioning
confidence: 99%